Integrating Productive Zakat Management for Sustainable Development: Strengthening Collaboration Between Baznas and Laz to Improve Mustahik Welfare - Wijaya, Andy Putra; Pambudi, Dwi Santosa; Setiawan, Iwan (Journal Research of Social Science, Economics, and Management, 2026)
The Sustainable Development Goals (SDGs) have established a comprehensive global framework for addressing multidimensional challenges related to poverty, inequality, and sustainable economic development. In Indonesia, productive zakat has increasingly been recognized as a strategic instrument of Islamic social finance capable of supporting the achievement of these goals through sustainable socioeconomic empowerment. This study examined the role of productive zakat management in advancing the SDGs by emphasizing institutional integration, effective governance, and collaborative partnerships among zakat management organizations and other development stakeholders. Using a qualitative approach based on a comprehensive review of relevant literature, policy documents, and empirical studies, the research explores the alignment between productive zakat programs and the objectives of sustainable development. The findings indicate that productive zakat contributes significantly to poverty alleviation, income generation, employment creation, human capital development, and the reduction of socioeconomic inequalities, particularly in relation to SDG 1 (No Poverty), SDG 3 (Good Health and Well-being), SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities). The study further demonstrates that the effectiveness of productive zakat depends on the integration of transparent and accountable governance, data-driven management, digital transformation, continuous beneficiary assistance, and institutional collaboration involving the National Zakat Agency (BAZNAS), Zakat Collecting Organizations (LAZ), government agencies, the private sector, and local communities.